Microstructure and Properties of Semi-Solid 7075 Aluminum Alloy Processed with an Enclosed Cooling Slope Channel - Zhaoqiang Li; Yongkun Li; Rongfeng Zhou; Lingzhi Xie; Qiansi Wang; Lingzhi Zhang; Qiang Ji; Bin Xu (Crystals, 2023)
In this study, an enclosed cooling slope channel (ECSC) was used to produce a semi-solid slurry of the 7075 aluminum alloy. The effects of the pouring temperature and the rate of cooling water on the microstructure of the semi-solid slurry were studied. The microstructure, solidification behavior, mechanical properties, and fracture mechanism of rheological squeeze casting (Rheo-SC) and liquid squeeze casting (LSC) samples were compared. The results indicate that lowering the pouring temperature and increasing the rate of cooling water can refine the crystals of the semi-solid slurry. The best process is a pouring temperature of 670 °C and a rate of cooling water of 200 L/h. The microstructure of the LSC samples was made up of coarse dendritic crystals, but the microstructure of the Rheo-SC samples was made up of almost spherical primary α1-Al and refined secondary α2-Al under this method. The ultimate tensile strength, yield strength, and elongation of the Rheo-SC samples were 238 MPa, 151 MPa, and 5.2%, respectively, which were 10%, 10.5%, and 44.4% higher than those of the LSC sample. The key factor contributing to the increased performance of the Rheo-SC samples is the combination of decreased casting flaws, strengthened grain refinement, and improved segregation.